Efficacy of various topical agents to prevent enamel demineralization - Priska Lestari Hendrawan; Erwin Siregar; Krisnawati Krisnawati (Dental Journal (Majalah Kedokteran Gigi), 2011)
Background: Enamel demineralization is a common and undesirable side effect of fixed appliance orthodontic treatment. Many sudies showed that the prevalence varied between 2–96%. There are many ways to prevent demineralization and increased remineralization such as oral hygiene instruction and by topical application such as acidulated phosphate fluor (APF) casein phospo peptide-amorphous calcium phosphate (CPP-ACP), casein phospo peptide-amorphous calcium phosphate plus (CPP-ACPF). Purpose: The purpose of this in-vitro study was to evaluate the efficacy of various topical agents to prevent enamel demineralization. Methods: Fourty extracted human premolars were allocated to 1 of 4 groups: 1.23% APF gel; 10% CPP-ACP paste; 10% CPP-ACPF paste; and untreated control. All samples were subjected to pH cycling treatment for 12 days through a daily procedure of demineralization solution with pH 4 for 6 hours and remineralization solution with pH 7 for 18 hours. Microhardness testing were done before and after pH cycling and the delta hardness values were determined. Results: APF, CPP-ACP and CPP-ACPF application significantly prevent lowering of enamel microhardness value compared with untreated control group. Kruskal-Wallis, ANOVA, Mann-Whitney U, Tukey and Bonferroni Post-Hoc multiple comparison test showed significant difference between mean delta microhardness value of CPP-ACPF and CPP-ACP group with APF group, but there is no significant difference between mean delta microhardness value of CPP-ACPF and CPP-ACP group. Conclusion: APF, CPP-ACP and CPP-ACPF prevent enamel demineralization. CPP-ACP and CPP-ACPF prevent demineralization more than APF.Latar belakang: Demineralisasi email merupakan efek samping negatif yang sering dijumpai pada perawatan ortodontik cekat. Beberapa penelitian menyatakan bahwa prevalensinya bervariasi 2–96 persen. Ada beberapa cara untuk mencegah demineralisasi dan meningkatkan remineralisasi, misalnya dengan instruksi kebersihan mulut dan menggunakan bahan topical aplikasi seperti acidulated phosphate fluor (APF) casein phospo peptide-amorphous calcium phosphate (CPP-ACP), casein phospo peptide-amorphous calcium phosphate plus (CPP-ACPF). Tujuan: Tujuan penelitian in vitro ini adalah untuk mengevaluasi efektivitas berbagai agen topikal untuk mencegah demineralisi email yang dilihat dengan uji kekerasan mikro permukaan email. Metode: emapat puluh gigi premolar yang sudah di ekstraksi dibagi dalam 4 kelompok: aplikasi gel 1,23% APF; aplikasi psta 10% CPP-ACP; aplikasi pasta 10% CPP-ACPF dan kelompok Kontrol. Semua sampel diberikan perlakuan siklus pH selama 12 hari yang terdiri dari perendaman dalam larutan demineralisasi dengan pH 4 selama 6 jan dilanjutkan dengan perendaman dalam larutan remineralisasi dengan pH 7 selama 18 jam. Uji kekerasan dilaku kan sebelum dan sesudah perlakuan serta diperoleh juga data delta kekerasan. Hasil: Semua aplikasi agen topikal tersebut dapat mencegah demineralisasi email secara signifikan dibandingkan kelompok kontrol. Kesimpulan: APF, CPP, ACP, dan CPD-ACPF mencegah demineralisasi enamel. CPP-ACP dan CPD-ACPF mencegah demineralisasi lebih baik dibanding APF.